2014
DOI: 10.1371/journal.pone.0111781
|View full text |Cite
|
Sign up to set email alerts
|

Transgene Detection by Digital Droplet PCR

Abstract: Somatic gene therapy is a promising tool for the treatment of severe diseases. Because of its abuse potential for performance enhancement in sports, the World Anti-Doping Agency (WADA) included the term ‘gene doping’ in the official list of banned substances and methods in 2004. Several nested PCR or qPCR-based strategies have been proposed that aim at detecting long-term presence of transgene in blood, but these strategies are hampered by technical limitations. We developed a digital droplet PCR (ddPCR) proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…A novel technology, ddPCR, was recently developed to enable the absolute quantification of nucleic acid target sequences. PCR with a TaqMan probe is performed within each droplet containing fragmented DNA, and the presence of the target gene is determined by counting the number of fluorescent signal-positive droplets 23, 24, 25. Based on this strategy, we established a new method for the absolute quantification of cells expressing the target gene.…”
Section: Discussionmentioning
confidence: 99%
“…A novel technology, ddPCR, was recently developed to enable the absolute quantification of nucleic acid target sequences. PCR with a TaqMan probe is performed within each droplet containing fragmented DNA, and the presence of the target gene is determined by counting the number of fluorescent signal-positive droplets 23, 24, 25. Based on this strategy, we established a new method for the absolute quantification of cells expressing the target gene.…”
Section: Discussionmentioning
confidence: 99%
“…By developing real‐time PCR tests to target exon‐exon junctions in cDNA, it has been shown that it is possible to detect very low amounts of a transgene in blood samples . A similar approach was employed by Moser et al in the development of a droplet digital PCR‐based method to detect an IGF1 transgene . At present, PCR methods hold the most promise for gene doping detection, although this approach requires design, meticulous optimisation and validation of a method specific for each target gene.…”
Section: Detectionmentioning
confidence: 99%
“…[31] The method allowed the detection of IGF-I transgenic elements for a 33-day period in DNA extracted from whole blood of 6 mice injected intramuscularly with AAV9-IGF-I elements. A duplex ddPCR protocol for IGF-I and EPO transgene elements was further developed to simultaneously detect two candidate genes for gene doping in a single assay.…”
Section: Detection Of Gene Dopingmentioning
confidence: 99%
“…Moreover, ddPCR can handle large amounts of background DNA in the reaction and is more tolerant to inhibitors and variation in amplification efficiencies. [31] These researches highlight the great effort that has been invested on the development of direct detection method of gene doping. It also demonstrates the will of anti-doping authorities to operate in a proactive way.…”
Section: Detection Of Gene Dopingmentioning
confidence: 99%